2014
DOI: 10.1002/ps.3942
|View full text |Cite
|
Sign up to set email alerts
|

Control of insect vectors and plant viruses in protected crops by novel pyrethroid-treated nets

Abstract: LLITNs of appropriate mesh size can become a very valuable tool in combination with biocontrol agents for additional protection against insect vectors of plant viruses under IPM programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…A few studies have evaluated LLISs for control of agricultural pests (Moreno et al, 2012;Dáder et al, 2015;Kuhar et al, 2017). In these studies, the applicability of LLISs for multiple economically important pests and their potential for reducing insecticide dependency in horticultural and open field agricultural systems were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have evaluated LLISs for control of agricultural pests (Moreno et al, 2012;Dáder et al, 2015;Kuhar et al, 2017). In these studies, the applicability of LLISs for multiple economically important pests and their potential for reducing insecticide dependency in horticultural and open field agricultural systems were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the first report concerning selectivity of these nets comes from our research group. Recent assays in small tunnels (8 m long × 6.5 m width × 2.6 m high) with a cucumber crop have shown that a bifenthrin‐treated net (3.8 g kg −1 ; 0.46 mm 2 hole size) is compatible with the parasitoid Aphidius colemani Viereck (Hymenoptera: Aphidiinae) and reduces Aphis gossypii Glover (Hemiptera: Aphididae) population density and the spread of two aphid‐transmitted viruses [ Cucumber mosaic virus (CMV) and Cucurbit aphid‐borne yellows virus (CABYV)] …”
Section: Introductionmentioning
confidence: 99%
“…In particular, pyrethroidincorporated nets applied as floating row covers, or 2-m high fences, have been shown to be efficacious for control of various lepidopteran and aphid pests of vegetables (Martin et al 2006, Licciardi et al 2008, Dader et al 2015, and are considered to be costeffective because they control multiple key pests, last multiple years, and because larger mesh sizes can be used compared with untreated row covers (Dader et al 2015). To our knowledge, the efficacy of LLINs for control of pestiferous stink bugs (Hemiptera: Pentatomidae) has not been investigated.…”
mentioning
confidence: 99%